Effect of Dosages and Temperatures on Simalungun Red Ginger (Zingiber officinale var. Rubrum) Ethanol Extract Dipping on Masculinization of Zebra Fish (Danio rerio) as a Model Fish - Eka Fitria Febriani; Maheno Sri Widodo; Abdul Rahem Faqih (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research